Comparison of sources and lines selected for drought resistance in common bean - Terán Santofimio, Henry; Singh, Shree P. (2002)
Drought is a major constraint to common bean (Phaseolus vulgaris L.) production worldwide. Our objectives were to (i) identify sources of drought resistant germplasm in common bean cultivars and (ii) compare drought resistant germplasm with lines selected from interracial and intergene pool populations. We included in this study 12 of the most promising drought resistant cultivars from race Durango and 11 from race Jalisco, nine drought resistant lines selected from interracial or intergene pool populations, and two drought resistant and two susceptible checks. The 36 genotypes were evaluated in drought-stressed (DS) and nonstressed (NS) environments in four cropping seasons between 1996 and 1998 at the International Center for Tropical Agriculture (CIAT), Palmira, Colombia. Drought stress reduced seed yield by 53%, 100-seed weight by 13%, and days to maturity by 3%. Race Durango cultivars had higher yield, larger seed weight, and earlier maturity than race Jalisco cultivars in DS and NS environments. Large variations within the two races were found for the three traits. Drought resistant selected lines out-yielded drought resistant checks by 44% in DS and 15% in NS and cultivars from race Durango by 48% in DS and 30% in NS and race Jalisco by 96% in DS and 46% in NS environments. Seed yield in DS was correlated negatively with the percent reduction (PR) because of drought stress and drought susceptibility index (DSI), whereas a positive correlation existed between PR and DSI. Drought resistant selected lines and race Durango cultivars had similar maturity. Mean 100-seed weight of selected lines (23 g) was less than race Durango (34 g) and race Jalisco cultivars (29 g). While new sources of drought resistance could be identified in races Durango and Jalisco, these drought resistant germplasm and selected lines derived from interracial and intergene pool populations should be utilized for improvement of drought resistance in common bean.